Development and in‐vitro characterization of a novel fetal vesicoamniotic shunt – The Vortex shunt. (27th January 2022) - Sheth, Kunj R.; Danzer, Enrico; Johnson, Eric; Wall, James K.; Blumenfeld, Yair J.
Abstract: Objectives: To develop and test a novel vesicoamniotic shunt (VAS) to treat fetal lower urinary tract obstruction (LUTO), decrease dislodgement and optimize shunt deployment in‐vitro. Methods: Vesicoamniotic shunt design objectives included: (1) robust and atraumatic fixation elements, (2) kink resistant conduit to adjust to fetal movement and growth, (3) one‐way pressure valve to facilitate bladder cycling, and (4) echogenic deployment visualization aids. The force to dislodge the novel Vortex shunt was compared with existing commercially available shunts in a bench‐top porcine bladder model. Sonographic echogenicity was evaluated with ultrasound‐guided deployment, and the shunt valve pressure measured. Results: A prototype novel Vortex shunt was developed using braided nitinol "umbrella‐type" ends with a kink‐resistant stem incorporating an internal one‐way valve. The peak force required to dislodge the Vortex shunt was significantly higher than commercially available shunts ( p  < 0.01). Shunt deployment in the bench‐top model was easily confirmed with ultrasound guidance and the brisk decompression of the inflated porcine bladder thereafter. In‐vitro valve gauge pressure testing mirrored bladder pressures in human LUTO cases. Conclusion: In‐vitro testing shows that the Vortex shunt may improve deployment, sonographic visualization, kink resistance, and dynamic size adjustment. Validation in preclinical animal models are warranted and currently underway. Key points: What is already known about this topic? Fetal vesicoamniotic shunting for lower urinary tract obstruction (LUTO) improves survival, but the risk for perioperative complications with currently available shunts is significant. What does this study add? In‐vitro testing shows that the novel Vortex vesico‐amniotic shunt may facilitate placement, improve ultrasonographic visualization, decrease dislodgement rate, improve kink resistance, and allow for dynamic size adjustment compared to the current shunt systems. The one‐way valve mechanism within the shunt may allow for an intermittent fetal bladder cycling and simulation of the natural voiding mechanism.